Accessibility of essential anticancer medicines for children in the Sichuan Province of China - Chen, Zhe; Li, Siyu; Zou, Kun; Li, Hailong; Zeng, Linan; Lu, Xiaoxi; Jia, Zhi-Jun; Cheng, Guo; Zhang, Lingli (Frontiers in Public Health, 2022)
Background Compared with high-income countries, the survival rate of childhood cancer is lower in low- and middle-income countries. Access to essential anticancer medicines is an indispensable component of pediatric cancer treatment, which is still a big challenge in low- and middle-income countries. Objective To assess the accessibility of essential anticancer medicines for children in public hospitals in the Sichuan Province of China. Methods Based on the data of the Sichuan Province Drug Use Monitoring Platform in 2020, a retrospective study was conducted to investigate the original brands and generics of 34 anticancer and three supportive essential medicines for children (a total of 97 specific strengths) in Sichuan Province. The availability, price, and affordability of surveyed medicines were evaluated in all 152 tertiary public hospitals (120 general hospitals, 31 children's hospitals, and one cancer hospital) that could diagnose and treat cancer for children. Results The average availability of generics and original brands was 18.5% and 2.6%, respectively. In regions with different gross domestic product (GDP) per capita levels, the average availability was similar, but the city with lower GDP per capita levels had fewer tertiary public hospitals. The prices of most original brands were higher than the lowest-priced generics, and the median price ratios of 31 lowest-priced generics and 16 original brands were 0.744 (P25 P75, 0.446 2.791) and 2.908 (1.719 6.465). After paying medical insurance for medicines, the affordability of essential anticancer medicines was improved. The monthly medicine cost did not exceed 10% of the monthly household income for 78.9% (30/38) of the lowest-priced generics and 50.0% (8/16) of the original brands. Conclusion The availability of lowest-priced generics was higher than original brands in public hospitals, but the availability of both was low, which was similar to previous studies in low- and middle-income countries. About half of the lowest-priced generics and 87.5% of the original brands cost more than 1.5 times the International Reference Price. Although the National Basic Medical Insurance greatly improved the affordability of essential anticancer medicines for children, higher subsidies for essential medicines for cancer treatment to limit catastrophic health expenditures are still recommended.